2019
DOI: 10.1002/anie.201906032
|View full text |Cite
|
Sign up to set email alerts
|

A Solid‐State Protein Junction Serves as a Bias‐Induced Current Switch

Abstract: As ample-type protein monolayer,t hat can be as tepping stone to practical devices,c an behave as an electrically driven switch. This feat is achieved using ar edox protein, cytochrome C( CytC), with its heme shielded from direct contact with the solid-state electrodes.A binitio DFT calculations,c arried out on the CytC-Aus tructure,s howt hat the coupling of the heme,t he origin of the protein frontier orbitals,tothe electrodes is sufficiently weak to prevent Fermi level pinning.T hus,e xternal bias can bring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
39
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 34 publications
2
39
1
Order By: Relevance
“…We used the OpenMX open source package, which is an efficient DFT code based on highly optimized numerical pseudoatomic orbitals (PAOs) [45,46]. We followed a similar approach to that we used in our previous work on gas-phase azurins [11] and cytochrome C [47]. The initial geometries for the DFT calculations were obtained from selected frames of the previous MD simulations, including the whole protein (1929 atoms) and the parts of the substrate and the tip closest to the protein.…”
Section: Methodsmentioning
confidence: 99%
“…We used the OpenMX open source package, which is an efficient DFT code based on highly optimized numerical pseudoatomic orbitals (PAOs) [45,46]. We followed a similar approach to that we used in our previous work on gas-phase azurins [11] and cytochrome C [47]. The initial geometries for the DFT calculations were obtained from selected frames of the previous MD simulations, including the whole protein (1929 atoms) and the parts of the substrate and the tip closest to the protein.…”
Section: Methodsmentioning
confidence: 99%
“…In the case of the metal-substituted proteins studied in [15], the low-temperature results showed evidence for coherent transport; it was suggested that both tunneling and hopping are possible, however, depending on the temperature and the type of junction [35]. For the present study, we are particularly interested in the possibility of fully-coherent transport, which was suggested by the temperature-independence of the conductance measured in several experiments based on azurins [8,11,23,26,32,[36][37][38][39]. In [34], various types of configurations were studied, in which an STM tip was contacted to a blue-copper azurin in three different ways: in blinking mode (in which the tip is kept at a fixed distance from the surface and the protein is allowed to attach to the tip spontaneously), via top indentation (in which the tip is brought closer to the protein) and by lateral indentation (in which the tip approaches the protein sideways).…”
Section: Introductionmentioning
confidence: 82%
“…Research in this field has been carried out on various fronts. On the one hand, remarkable effort has been made to understand the exact nature of the charge transfer mechanism in protein-based junctions as well as to identify the components which play the dominant role in the transport process [8][9][10][11]. On the other hand, the possibility of modifying the conductance properties by the insertion of mutations [3,10,11] has also attracted a lot of interest.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, it has been experimentally and theoretically proved that it is possible to tune molecular electron transfer rates in electron transfer proteins (ETpr's) through (i) chemical modifications and changes in the redox center, as well as the locations of the donor, the acceptor, and the bridge moieties within the ETpr's structure [220,[224][225][226][227][228] (ii) modifying the solvent environment [229], and importantly, (iii) orientation relative to the electrode and changing the strength of the protein-electrode coupling [230][231][232]. The study of large-area protein-based molecular electronic devices has been carried out mainly by the self-assembly method [148,149] via an appropriate linker. DNA has also focused the interest of researchers in the molecular electronics community due to several reasons, including (i) superior self-assembly properties [233,234]; (ii) its unique electrical properties [235], and (iii) its potential use in bioelectronics devices.…”
mentioning
confidence: 99%